Inventing ideas : patents, prizes, and the knowledge economy - Khan, B. Zorina (Oxford University Press, 2020)
"This books shows how and why the ideas of creative individuals promote progress. The insights are based on original archival research regarding over one hundred thousand inventors, patented inventions, and innovation prizes in Europe and the United States during industrialization. This systematic empirical analysis across time and place and institutions provides an extensive microfoundation for understanding technological change and long-run macroeconomic growth. British and French policies favoured "administered innovation systems," in which elites, administrators or panels made key economic decisions about inducement prizes, rewards and the allocation of resources. European institutions generated returns that were misaligned with economic value and productivity, and perpetuated socioeconomic inequality. Europe fell behind when the negative consequences of such top-down administered systems accumulated and reduced comparative advantage. The modern knowledge economy emerged when, for the first time in world history, an intellectual property clause was included in a national Constitution, in the United States. This strong endorsement for open-access property rights and unfettered markets in ideas reflected a revolution in thinking about the sources of creativity and technical progress. U.S. global industrial ascendancy was a direct outcome of its decentralized market-oriented institutions, which fostered diversity in ideas and innovations, the diffusion of information and disruptive technologies, and sustained endogenous growth"--